Rare lichens and lichenicolous fungi from the Zacharovanyi Krai National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What rare lichens have been found recently in Zacharovanyi Krai National Nature Park? Location: Zakarpattia region, Ukraine Materials and methods: field research, microscope technique Nomenclature: Index Fungorum Results: Thirteen rare lichen species Absconditella sphagnorum, Arthonia granitophila, Dendrographa latebrarum, Enterographa zonata, Halecania viridescens, Ionaspis lacustris, Fellhanera subtilis, Gyrographa gyrocarpa, Haematomma ochroleucum, Stereocaulon dactylophyllum, S. pileatum, Trapelia corticola, Zamenhofia pseudohibernica, along with two species of lichenicolous fungi, Taeniolella friesii and Zyzygomyces physciacearum, have been newly recorded for the Zacharovanyi Krai National Nature Park. These species were known only from a scattered localities in Ukraine, mainly in the Carpathians. The species Dendrographa latebrarum is reported here for the first time from the Ukrainian Carpathians. Arthonia granitophila, Halecania viridescens and Taeniolella friesii were previously known only from a single location in the Ukrainian Carpathians. Ionaspis lacustris and Stereocaulon dactylophyllum each previously known from just one locality in Ukraine, have now been rediscovered in the Volcanic Carpathians after 73 and 93 years, respectively. Detatiled data on the localities and occurrences of all species within Ukraine is provided.
Keywords: biodiversity, fungi, species, Zakarpattia region, Ukraine